Increasing the Bioavailability of Phosphate by Using Microorganisms - A. A. A. U. Aberathna; D. A. Satharasinghe; A. P. Jayasooriya; R. N. Jinadasa; S. Manopriya; B. P. A. Jayaweera; C. A. N. Fernando; W. A. D. V. Weerathilake; G. A. Prathapasinghe; J. A. Liyanage; J. M. K. J. K. Premarathne (International Journal of Agronomy)
Phosphorous (P) is a nonrenewable and one of the most important macronutrients for all living organisms. The formation of complexes with cations such as Al, Fe, and Ca reduces the solubility of P leading to limiting the absorption of P by plants. Therefore, we need to apply excessive amounts of P through conventional fertilizers. However, plants can use only a small portion of P of these added fertilizers whenever those become unavailable. Therefore, utilizing excess amounts of phosphate as fertilizers can lead to various environmental issues like eutrophication. Phosphate-solubilizing microorganisms (PSM) have the ability to solubilize soil phosphate through the production of organic acids, inorganic acids, enzymes, protons, siderophores, and exopolysaccharides resulting in the absorption of P by plants. The application of PSM has the potential to be used as an efficient, eco-friendly, and sustainable approach that can replace traditional fertilizers. This review aimed to give an overview of the diversity of PSM, methods of P solubilization, current trends, and technological advances that can assist in using PSM to achieve Sustainable Development Goals (SDGs).